Peluang Pegawai Negeri Sipil Perempuan dalam Pengisian Jabatan Struktural di Pemerintah Kabupaten Lamandau, Kalimantan Tengah (Suatu Studi Praktik Kesetaraan Gender) - Bikhusnil Ummah; Puji Astuti; Lusia Astrika (Journal of Politic and Government Studies, 2014)
AbstractGender equality is a study that has long been of concern to the Government of Indonesia. Of the Legislature, there has introduced a quota system as a form of affirmative action for women to be able to occupy the parliament. But on the bureaucracy there is still no consistent effort from the government to help the female civil servants to occupy strategic positions in the bureaucracy. In this study, researchers focused the research in a district result of the expansion that is Lamandau District. This study is focused to see the opportunities of women civil servants in to occupy the structural positions in the Lamandau District and to know what supporting and inhibiting factors.Issues to be discussed here is the opportunity of women civil servants in filling structural possition in Lamandau District Government, Central Borneo. From the background mentioned earlier, the researcher wants to conduct research in order to obtain a deeper understanding of the issue, so that the research methods that will be used by researchers is a qualitative research method with descriptive type.From the results of research in the field, all informants agreed that the opportunities and access to filling the structural possition between men and women civil servants is the same. The imbalance amount of Structural Official based on gender because there is not many women civil servants fulfilling List Sort Ranks (DUK) condition. Supporting factors for structural occupation for a women civil servants is the notion that women are more conscientious, diligent, and tenacious. While the factors that are inhibiting more to reproductive factors, lack of support from family, and the technical factor such as access to Leadership Training places away and the duration of training.That needs to be addressed here is the consistency of government to regulate career civil servants coaching pattern because there isn’t detailed pattern to manage civil servants’ career. Promotion needs to be done such as the possition auction to ensure the continuity of career civil servants. In addition, should be instilled in every women civil servant is the awareness and willingness of women to be able to achieve the highest career in order to produce a gender prespective decisions.Keywords: Gender equality, structural position, career, women civil servants, bureaucratic.